Advances in symptomatic therapy for left ventricular non-compaction in children - Li, Dong; Wang, Ce (Frontiers in Pediatrics, 2023)
Left ventricular non-compaction is a complex cardiomyopathy and the third largest childhood cardiomyopathy, for which limited knowledge is available. Both pathogenesis and prognosis are still under investigation. Currently, no effective treatment strategy exists to reduce its incidence or severity, and symptomatic treatment is the only clinical treatment strategy. Treatment strategies are constantly explored in clinical practice, and some progress has been made in coping with the corresponding symptoms because the prognosis of children with left ventricular non-compaction is usually poor if there are complications. In this review, we summarized and discussed the coping methods for different left ventricular non-compaction symptoms.